Difference between the Decrease in P1NP Concentration and MRSS Within 3 Months Treatment of Systemic Sclerosis - Devy Priyantini Hanafi; Sumartini Dewi; Andri Reza Rahmadi (Indonesian Journal of Rheumatology, 2021)
Introduction: Systemic sclerosis is characterized by extensive and progressive organ fibrosis leads to organ failure and death. Progression of skin thickening is a predictor of morbidity and mortality. Due to the limitation of modified Rodnan skin score (MRSS) sensitivity in detecting small changes in skin fibrosis, thus we proposed Procollagen Type I N-Terminal Propeptide (P1NP) as potential biomarker. This study aimed to analyze the difference between the decrease in P1NP concentration and MRSS within 3 months treatment of systemic sclerosis. Methods: We conducted a retrospective cohort of paired numerical comparative analytic methods, as follow up of a study done by Vincent et al. and Dewi et al. Analyzis of MRSS changes and serum P1NP concentrations were done prior to treatment (baseline), and on week 4th, 8th and 12th treatment. Result: Fifty-nine subjects were enrolled in the study. We analyzed the results of P1NP and MRSS at 4th, 8th and 12th weeks of treatment, there was a significant decrease in mean rank of P1NP and MRSS (p=0.033 and <0.001). The effect of MRSS change was greater than P1NP. The highest decreasing effect of MRSS was obtained at week 8th (?2 = 0.424, 42.4% decrease effect), and the largest decrease effect of P1NP was obtained at week 12th (?2 = 0.120; 12% decrease effect). Conclusion: There was a difference in decreasing P1NP concentrations and MRSS in systemic sclerosis within 3 months of observation. MRSS showed a larger decrease in change than P1NP after treatment.